2020
DOI: 10.17650/1726-9784-2020-19-3-12-20
|View full text |Cite
|
Sign up to set email alerts
|

Phytoadaptogens in the Tumours Biotherapy and Geriatrics (Part 2)

Abstract: Phytoadaptogens (ginseng, eleutherococcus, rhodiola rosea, aralia, etc.) have a wide spectrum of biological activity, supporting the body in a state of nonspecific increased resistance to stress. The second part of the review provides information of the phytoadaptogens normalizing effects on the cardiovascular system. Analyzes current data on the antitumor properties of phytoadaptogens in relation to the effect on the onset and development of tumours, metastasis, recurrence, development of cytostatic disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…Experimental and clinical studies of MPhA have revealed antimutagenic (which is important for primary cancer prevention, or chemoprophylaxis), antitumor (essential for secondary prevention), radioprotective, hormone‐modulating, antioxidant, neuroprotective, immunomodulatory, including adhesive and interferon‐inducing effects (which are important for tertiary cancer prevention). All of these activities promote survival and the quality of a patient‘s life [32] . By the way, adaptogens which are known to promote longevity affect the neuro‐endocrine‐immune system including antimutagenic, immune‐ and hormone‐modulating, neuroprotective and antiparkinsonian properties [15] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Experimental and clinical studies of MPhA have revealed antimutagenic (which is important for primary cancer prevention, or chemoprophylaxis), antitumor (essential for secondary prevention), radioprotective, hormone‐modulating, antioxidant, neuroprotective, immunomodulatory, including adhesive and interferon‐inducing effects (which are important for tertiary cancer prevention). All of these activities promote survival and the quality of a patient‘s life [32] . By the way, adaptogens which are known to promote longevity affect the neuro‐endocrine‐immune system including antimutagenic, immune‐ and hormone‐modulating, neuroprotective and antiparkinsonian properties [15] …”
Section: Resultsmentioning
confidence: 99%
“…As a result, 70 major phytocomponents have been selected in the MPhA composition. Pharmacological and toxicological characteristics of MPhA have been investigated in vitro, in vivo and in clinical studies [30–32] . A wide range of pharmacological effects (adaptogenic, antitumor, immunomodulatory, antimutagenic, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…В данном случае следует подчеркнуть, что противоопухолевые эффекты получены с помощью препаратов, в состав которых входят фитоадаптогены, обладающие адгезиогенным действием [56,57].…”
Section: значение концепцииunclassified